2016
DOI: 10.1590/2317-1782/20162015048
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing endoscopy findings in Huntington's disease: a case report

Abstract: Huntington's disease (HD) is a degenerative genetic disorder with autosomal-dominant transmission. The triad of symptoms of this disease consists of psychiatric disorders, jerky movements, and dementia. Oropharyngeal dysphagia, which is more evident with disease progression, is also present. Few studies have addressed the swallowing characteristics using objective analysis in this population. The purpose of this research was to describe the swallowing endoscopic findings of the pharyngeal phase in HD. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The swallowing characteristics in HD as demonstrated by the FEES study included delay in the initiation of the swallowing reflex with initiation of the reflex only when the food bolus reached the vallecula, solid food residues, preand post-swallowing spillage to the pharynx, and rarely laryngeal penetration and/or aspiration These findings are in accordance with a recent study by Alves et al, 16 who reported posterior oral spillage of liquids and nectar, small amounts of pharyngeal residues, and no laryngeal penetration or aspiration in 2 HD patients undergoing FEES studies. Food residues in HD patients were also noted in other studies that utilized videofluoroscopy to evaluate dysphagia.…”
Section: Discussionsupporting
confidence: 90%
“…The swallowing characteristics in HD as demonstrated by the FEES study included delay in the initiation of the swallowing reflex with initiation of the reflex only when the food bolus reached the vallecula, solid food residues, preand post-swallowing spillage to the pharynx, and rarely laryngeal penetration and/or aspiration These findings are in accordance with a recent study by Alves et al, 16 who reported posterior oral spillage of liquids and nectar, small amounts of pharyngeal residues, and no laryngeal penetration or aspiration in 2 HD patients undergoing FEES studies. Food residues in HD patients were also noted in other studies that utilized videofluoroscopy to evaluate dysphagia.…”
Section: Discussionsupporting
confidence: 90%
“…Dysphagia in HD has been investigated by subjective and objective swallowing evaluation tests and described in case reports and case series 1 , 3 6 . The Huntington’s Disease Dysphagia Scale (HDDS), a self-report questionnaire specifically designed to assess swallowing in HD, has demonstrated good construct.…”
Section: Introductionmentioning
confidence: 99%
“…In the largest study to date, dysphagia was objectively evaluated by means of videofluoroscopic swallowing study (VFSS) in a cohort of 35 HD patients with moderate-to-advanced stage disease 8 . More recently, fiberoptic endoscopic evaluation of swallowing (FEES) was described in small patient cohorts 6 , 9 . The studies underscored the importance of dysphagia in HD patients with moderate-to-advanced stage disease, but it remains unclear whether dysphagia affects patients at an early stage and when penetration/aspiration is likely to occur in HD progression.…”
Section: Introductionmentioning
confidence: 99%
“…We selected a total of 22 studies (Alves et al, 2016; Azambuja et al, 2012; Boyle et al, 2008; Bradford et al, 2004; Carlozzi et al, 2021; Deniz et al, 2011; Diehl et al, 2019; Dodderi & Micheal, 2016; da Fonseca & Walker, 1993; Hamakawa et al, 2004; Hertrich & Ackermann, 1994; Hino et al, 2017; Kagel & Leopold, 1992; Keage et al, 2020; Manor et al, 2019; Oh et al, 2011; Reilmann et al, 2010; Reyes et al, 2014; Saft et al, 2013; de Tommaso et al, 2015; Vogel et al, 2012; Yoon et al, 2006), 12 research articles (Azambuja et al, 2012; Carlozzi et al, 2021; Diehl et al, 2019; Hertrich & Ackermann, 1994; Kagel & Leopold, 1992; Keage et al, 2020; Manor et al, 2019; Reilmann et al, 2010; Reyes et al, 2014; Saft et al, 2013; de Tommaso et al, 2015; Vogel et al, 2012), and 10 case reports (Alves et al, 2016; Boyle et al, 2008; Bradford et al, 2004; Deniz et al, 2011; Dodderi & Micheal, 2016; da Fonseca & Walker, 1993; Hamakawa et al, 2004; Hino et al, 2017; Oh et al, 2011; Yoon et al, 2006). The latest study was from 2021 (Carlozzi et al, 2021), while the oldest was from 1992 (Kagel & Leopold, 1992).…”
Section: Resultsmentioning
confidence: 99%